1966
DOI: 10.1104/pp.41.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Flow Relations in Vascular Bundles of the Tomato Plant

Abstract: .Sumtnary. In the tomato plant water flows through primary xylenm in accordanice with Poiseuille's law. This relation and the analogy between Poiseuille's and Ohm's law were employed to calctulate rates of flow and differences in pressure within vascular bunidles when transpiration rates from individual leaves were known. The resistance of vascular bundles to flow was calculated from a modificationl of Poiseuille's law and from neasurements of vessels in all bundles. The rates of flow in all bundles were deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 9 publications
2
35
1
Order By: Relevance
“…The dye always accumulated uniformly in each of the three leaflets of leaf 5. Our results suggest that patterns in vascular connectivity of potato are similar to those reported in tomato (Dimond 1966;Orians et al 2000): the right half of leaf 2, left half of leaf 3, and all of leaf 5 share direct vascular connections with the export leaf, whereas leaves −1, 1, and 4 have minimal vascular connections with the export leaf (Fig. 2B).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The dye always accumulated uniformly in each of the three leaflets of leaf 5. Our results suggest that patterns in vascular connectivity of potato are similar to those reported in tomato (Dimond 1966;Orians et al 2000): the right half of leaf 2, left half of leaf 3, and all of leaf 5 share direct vascular connections with the export leaf, whereas leaves −1, 1, and 4 have minimal vascular connections with the export leaf (Fig. 2B).…”
Section: Resultssupporting
confidence: 71%
“…Vascular connectivity among leaves is based on their phyllotactive arrangement. In general, leaves that are vertically aligned in their phyllotactive arrangement share direct vascular connections and transport the greatest amounts of vascular contents, leaves with adjacent alignment share partial vascular connections and transport less, and leaves with an opposite alignment lack vascular connections and transport the least (Dimond 1966;Orians et al 2000;Orians 2005). Vascular architecture can also refer to the arrangement of vascular bundles in plant stems.…”
Section: Introductionmentioning
confidence: 99%
“…However, since only the basal half of a leaf was placed in the pressure chamber, it appears more likely in the present case that the major resistance occurred within the petiole or at the nodal junction between the stem and leaf. Dimond (5) in an anatomical study of the water-conducting tissues of a tomato plant showed a marked change in resistance to flow between the stem and petiole in all leaves except the small upper ones. The change in resistance was the result of a decrease in the radius of the xylem vessels and a reduction in the number of vascular bundles.…”
Section: Resultsmentioning
confidence: 99%
“…The Poiseuille equation has been widely used to predict conductivity in the xylem. Results, however, have been variable, with measured conductivity and flows ranging from 20-100% of theoretical values (Dimond, 1966 ;Calkin et al, 1986 ;Hargrave et al, 1994).…”
Section: Axial Hydraulic Conductivitymentioning
confidence: 99%